Creating brand communities: a phenomenological study on media and the psychology of brand magic - Goodwin, Jill Suzanne, author; Luft, Gregory N., advisor; Switzer, Jamie S., committee member; Sivakumar, Gayathri, committee member; Donavan, D. Todd, committee member (Colorado State University. Libraries, 2017)
Understanding the complexities of the consumer-brand relationship is an ongoing area of study in multiple fields. Stemming from the notion that brands convey cultural meaning, brand community studies focus specifically on the process of meaning creation. The traditional focus of brand community research has been on social interaction. However, newer research points to the psychological formation of brand communities in the absence of social interaction. The psychological sense of brand community (PSBC) model was created to account for this newer area of research. Mental models are the cognitive model individuals form to interact with the world around them. Based in psychology, mental model research postulates that individuals must first be able to internally represent their external world in order to interact with it. Mental model theory provides a foundation for insight to the individual's reality of the brand community relationship at the social and psychological level. Thus, this study will use a qualitative phenomenological approach to elicit and explore the expressed mental models of members that self-identify with a brand community when exposed to branded media. In particular, this study centers around the Disney brand and how Disney's use of video advertisements activates PSBC among a loyal following. By using a brand exemplar to study this phenomenon, common themes of the consumer-brand relationship are revealed that give insight to the types of internal representations of external reality elicited by branded media exposure. By gaining a better understanding of the difference between psychological and social brand communities, media communication scholars can gain a deeper understanding of how the types of messages created for a brand can foster a sense of relationship with the brand.